2012
DOI: 10.3390/molecules17010452
|View full text |Cite
|
Sign up to set email alerts
|

A Biosorption Isotherm Model for the Removal of Reactive Azo Dyes by Inactivated Mycelia of Cunninghamella elegans UCP542

Abstract: The biosorption of three reactive azo dyes (red, black and orange II) found in textile effluents by inactive mycelium of Cunninghamella elegans has been investigated. It was found that after 120 hours of contact the adsorption led to 70%, 85%, 93% and 88% removal of reactive orange II, reactive black, reactive red and a mixture of them, respectively. The mycelium surface was found to be selective towards the azo dyes in the following order: reactive red > reactive black > orange II. Dye removal from a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 28 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…Decolouration can be accomplished by adsorption or enzymatic degradation. Inactivated mycelia of Cunninghamella elegans (Ambrosio et al, 2012), T. versicolor lyophilized biomass (Erden et al, 2011), T. versicolor (Baccar et al, 2011) or Fusarium solani non-viable cells (Abedin, 2008) are more efficient than materials such as activated carbon or amberlite. Adsorption is enhanced at pH 2e3 (Erden et al, 2011;Renganathan et al, 2006;Bakshi et al, 2006;Iqbal and Saeed, 2007;Pajot et al, 2011;Maurya et al, 2006), which is probably due to electrostatic attractions between charged dye molecules and the charged cell surface (Erden et al, 2011;Kaushik and Malik, 2009).…”
Section: Decolouration Of Azo Dyes Using Filamentous Fungimentioning
confidence: 99%
“…Decolouration can be accomplished by adsorption or enzymatic degradation. Inactivated mycelia of Cunninghamella elegans (Ambrosio et al, 2012), T. versicolor lyophilized biomass (Erden et al, 2011), T. versicolor (Baccar et al, 2011) or Fusarium solani non-viable cells (Abedin, 2008) are more efficient than materials such as activated carbon or amberlite. Adsorption is enhanced at pH 2e3 (Erden et al, 2011;Renganathan et al, 2006;Bakshi et al, 2006;Iqbal and Saeed, 2007;Pajot et al, 2011;Maurya et al, 2006), which is probably due to electrostatic attractions between charged dye molecules and the charged cell surface (Erden et al, 2011;Kaushik and Malik, 2009).…”
Section: Decolouration Of Azo Dyes Using Filamentous Fungimentioning
confidence: 99%
“…Amera et al (2012) Table 2). Ambrósio et al (2012) reported that Freundlich isotherm yielded a better linear fit (R 2 >0.99) than the Langmuir model (R 2 >0.95) suggesting that the adsorption surface presents heterogeneity. The mycelial surface of Cunninghamella elegans was observed to be more selective towards the red dye followed by reactive black and orange II.…”
Section: +mentioning
confidence: 99%
“…Application of dead fungal biomass obtained from R. arrhizus to remove textile dyes from industrial waste water is attractive due to its cheap and constant supply from industrial fermentation processes, high removal rates, easy storage and regenerative potential [11]. Some researchers have demonstrated the high dye binding capacity of R. arrhizus which exceeds that of some commercial ion exchange resins or activated carbon [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, low-cost biosorbents with high adsorption capacities such as waste materials from large-scale industrial operations, natural materials derived from agriculture, microbial biosorbents such as Corynebacterium glutamicum, Escherichia coli, Pseudomonas luteola and Rhizopus arrhizus have gained attention [9,10]. A major advantage of biosorption is that it can be used in situ and integrated with many systems in the most eco-friendly manner [11].…”
Section: Introductionmentioning
confidence: 99%